In-silico ADME prediction and molecular docking study of novel benzimidazole-1,3,4-oxadiazole derivatives as CYP51 inhibitors for antimicrobial activity - Shivanand Kolageri; S Hemanth; Mahesh Parit (Creative Pharma Assent, 2022)
A class of innovative benzimidazole-1,3,4-Oxadiazole derivatives is a significant heterocyclic molecule for therapeutic development. In heterocyclic chemistry, the novel 1,3,4-Oxadiazole nucleus has a wide range of uses, including antibacterial, treatment. Molecular docking is frequently employed in contemporary drug design to comprehend drug-receptor interaction. Swiss dock, PyRx, and discovery studio visualizer (DSV) tools were used to predict in-silico ADME properties. In the current investigation, substituted benzimidazole-1,3,4-Oxadiazole derivatives were taken for docking studies against 6AYB an Naegleria fowleri CYP51-ketoconazole complex. The main objective of the study is to perform docking of the selected benzimidazole-1,3,4-oxadiazole derivatives on the protein and compare the docking score with standard ketoconazole. The molecular docking study was conducted using PyRx and the discovery studio visualizer (DSV) program, Naegleria fowleri CYP51-ketoconazole complex (6AYB) was obtained from the protein data bank (PDB) site. It was found that the docking score of all sixteen 1,3,4-Oxadiazole compounds ranged from -8.1 to -8.9 Kcal/mol. The novel benzimidazole with 1,3,4-Oxadiazole derivatives has been found to possess antibacterial properties, many substituted 1,3,4-Oxadiazole derivatives have been reported for the activity